Inflammatory Arthritis Induced by Pembrolizumab in a Patient With Head and Neck Squamous Cell Carcinoma - Spathas, Nikolaos; Economopoulou, Panagiota; Cheila, Myrto; Kotsantis, Ioannis; Fanouriakis, Antonis; Kassara, Dimitra; Psyrri, Amanda (Frontiers in Oncology, 2018)
Introduction: T cell checkpoint inhibitors targeting Programmed cell Death protein-1 (PD-1) have emerged as novel immunotherapy agents showing remarkable efficacy in head and neck squamous cell carcinoma (HNSCC). Despite important clinical benefits, they are associated with side effects that occur as a consequence of general immunological stimulation due to loss of T cell inhibition. Herein, we report the unusual case of inflammatory arthritis induced by anti-PD-1 agent pembrolizumab. Case report: A 55-years old male was treated with pembrolizumab at a dose of 200 mg every 3 weeks for a metastatic hypopharyngeal carcinoma. Following two cycles of immunotherapy, and while complete response of lung metastases was achieved, the patient presented with stiffness, swelling and pain of the right knee. Clinical examination and synovial fluid analysis revealed a seronegative inflammatory arthritis. Pembrolizumab therapy was interrupted and low-dose prednisone was administered with remarkable clinical improvement. Pembrolizumab was reintroduced, but after the fifth cycle, the patient developed inflammatory polyarthritis involving both knees and interphalangeal joints of both hands resulting in severe clinical deterioration. At that time, treatment with pembrolizumab was permanently discontinued. High-dose prednisone and methotrexate treatment led to remission of clinical symptoms. Conclusion: Pembrolizumab-induced inflammatory arthritis is an unusual rheumatic immune-related adverse event that physicians are likely to encounter as ICI use expands. Multidisciplinary management and rheumatology consultation are necessary to provide immediate treatment and avoid permanent joint damage.